2006
DOI: 10.1248/bpb.29.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcineurin Inhibitors on Pharmacokinetics of Mycophenolic Acid and Its Glucuronide Metabolite during the Maintenance Period Following Renal Transplantation

Abstract: Mycophenolic acid (MPA), the active metabolite of mycophenolate mofetil (MMF) has been introduced into renal transplant immunosuppressant protocols in combination with calcineurin inhibitors (CNIs) and steroids. This study compared the pharmacokinetic profiles of MPA and its major metabolite MPA glucuronide (MPAG) in combination with tacrolimus (TAC) or cyclosporine (CyA) during the maintenance period (Ͼ6 months) following renal transplantation. There was no difference between TAC and CyA-treated groups in MPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 33 publications
0
26
2
Order By: Relevance
“…9,34,41,42 In the present investigation, exposure to AcMPAG was somewhat higher in liver transplant recipients on low-dose CSA than in those patients on low-dose TAC, although this did not reach statistical significance. However, AcMPAG concentrations at 2-hour postdose, the time point at which the maximum CSA and TAC concentrations occurred, and also at 4-hour postdose were significantly higher in those patients on CSA.…”
Section: Discussioncontrasting
confidence: 76%
“…9,34,41,42 In the present investigation, exposure to AcMPAG was somewhat higher in liver transplant recipients on low-dose CSA than in those patients on low-dose TAC, although this did not reach statistical significance. However, AcMPAG concentrations at 2-hour postdose, the time point at which the maximum CSA and TAC concentrations occurred, and also at 4-hour postdose were significantly higher in those patients on CSA.…”
Section: Discussioncontrasting
confidence: 76%
“…18 However, several studies have reported that CyA affects the pharmacokinetics of MPA and MPAG. 15,[21][22][23] It remains to be clarified why the MPA AUC in LN patients was similar to that in KT recipients. In this study, the LN patient group had lower serum creatinine levels, higher doses of prednisolone, absence of CNI medication, and a higher proportion of women.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to these studies demonstrating no or an inverse correlation between renal function and MPA exposure, other studies have associated renal impairment with higher MPA exposure (27)(28)(29)(30)(31)(32) (Table 1). The reason for these inconsistencies in the impact of renal function on MPA exposure is not clear.…”
mentioning
confidence: 85%